Characterization of Biominerals in Cacteae Species by FTIR - Alejandro De la Rosa-Tilapa; Agustín Maceda; Teresa Terrazas (Crystals, 2020)
A biomineral is a crystalline or amorphous mineral product of the biochemical activity of an organism and the local accumulation of elements available in the environment. The cactus family has been characterized by accumulating calcium oxalates, although other biominerals have been detected. Five species of Cacteae were studied to find biominerals. For this, anatomical sections and Fourier transform infrared, field emission scanning electron microscopy and energy dispersive x-ray spectrometry analyses were used. In the studied regions of the five species, they presented prismatic or spherulite dihydrate calcium oxalate crystals, as the predominant biomineral. Anatomical sections of Astrophytum asterias showed prismatic crystals and Echinocactus texensis amorphous silica bodies in the hypodermis. New findings were for Ariocarpus retusus subsp. trigonus peaks assigned to calcium carbonate and for Mammillaria sphaerica peaks belonging to silicates.